2016
DOI: 10.4172/2161-119x.1000278
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Trait, Malaria and Sensorineural Hearing Loss–A Case-Control Study from São Tomé and Príncipe

Abstract: Background: Hearing loss is a problem with higher incidence in South Asia, Asia Pacific and sub-Saharan Africa. In these countries there is also associated history of anemia and malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Thus, we expect that this value corresponds to the estimated prevalence of SCT in the whole population between 15 and 49 years in São Tomé e Príncipe. This prevalence is accordant to the previous studies in the country [ 13 15 ]. Ranking high in the interval of prevalence found in West Africa [ 2 ], this highlights the need for São Tomé e Príncipe to participate in the regional effort to tackle the disease [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we expect that this value corresponds to the estimated prevalence of SCT in the whole population between 15 and 49 years in São Tomé e Príncipe. This prevalence is accordant to the previous studies in the country [ 13 15 ]. Ranking high in the interval of prevalence found in West Africa [ 2 ], this highlights the need for São Tomé e Príncipe to participate in the regional effort to tackle the disease [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…São Tomé e Príncipe, the archipelagic country in the Gulf of Guinea, still lacks official numbers on carriers and patients. Three previous hospital-based studies point to an SCT prevalence between 13.00% [ 13 ], 14.10% (plus 1.92% of Hemoglobin C) [ 14 ] and 19.40% [ 15 ]. A revision of the 2021 Global Burden of Disease estimated that SCD was the 5th cause of under-five mortality in the country [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that most severe form of hearing impairment (SNHL) was among the HbSS patients; thus, their study could not correlate hearing status with severity of SCT. Caroca and de Lima 31 in São Tomé and Príncipe population observed no increase (control=34 vs test=20 cases) in the proportion of SCT participants with hearing impairment using PTA when compared with HbAA participants, and so they would not conclude that SCT predisposes to the development of hearing impairment. However, their study design was retrospective with multiple confounders.…”
Section: Discussionmentioning
confidence: 89%